Revisiting Malaya uncovering historical and political thoughts in Nusantara - Su, Yingxin; Wei, Yueping (Malaysian studies series, 2021)
"The contents of this volume go a long way to furthering our understanding of many dimensions of the difficult issues involved, including the national question." Jomo Kwame Sundaram. The concept of 'Malaya' continues to exert a powerful draw on our imagination, steeped in exotism and Orientalist reductions. Even decades after the end of the colonial period, it casts a long shadow over modern-day Malaysia and the rest of maritime Southeast Asia. How can we understand this constantly transforming subjectivity? Most importantly, how do we recognise the continuation of problems inherited from colonisation, and overcome these distorted discourses? Revisiting Malaya seeks to explicitly address these problems, taking regional Cold War divisions and historical links and fractures into consideration. By considering a wide range of topics presented by speakers at two landmark conferences, from the propaganda efforts of the Malayan Film Unit to the visionary writings of visionaries and revolutionaries, ranging from Usman Awang to Tan Malaka, this book uses 'Malaya as method' to better understand historical and contemporary realities.